Inflammation and Macular Oedema after Pars Plana Vitrectomy - Vito Romano; Martina Angi; Fabrizio Scotti; Renata del Grosso; Davide Romano; Francesco Semeraro; Paolo Vinciguerra; Ciro Costagliola; Mario R. Romano (Mediators of Inflammation)
Cystoid macular oedema (CMO) is a major cause of reduced vision following intraocular surgery. Although the aetiology of CMO is not completely clarified, intraocular inflammation is known to play a major role in its development. The macula may develop cytotoxic oedema when the primary lesion and fluid accumulation occur in the parenchymatous cells (intracellular oedema) or vasogenic oedema when the primary defect occurs in the blood-retinal barrier and leads to extracellular fluid accumulation (extracellular oedema). We report on the mechanisms of CMO formation after pars plana vitrectomy and associated surgical procedures and discuss possible therapeutic approaches.